Effects of three months of vitamin D, creatine, and polyunsaturated fatty acids supplementation in body composition and biochemical parameters in professional soccer players - Moya-Amaya, H.; Lara-Padilla, E.; Rojano-Ortega, D.; Molina-Lopez, A.; Berral-Aguilar, A. J.; Berral-De la Rosa, C. J.; Berral-De la Rosa, F. J. (Medicina dello Sport, 2021)
BACKGROUND: Monitoring of biochemical markers related to inflammation and muscle damage in high-performance sports is increasingly used; sometimes, these markers are interrelated with other of body composition. The main objective of this study was to analyze the effects of a specific nutritional supplementation on body composition and on markers of muscle damage and inflammation in professional soccer players during part of a competitive season.